Best Practices for Promoting Science Student Teachers’ Technological Pedagogical Content Knowledge (TPACK) in Life Science - Jituafua, Artitaya (Jurnal Pendidikan IPA Indonesia, 2024)
This study aimed to identify the best practices for promoting 22 science student teachers’ technological pedagogical content knowledge (TPACK) in life science at a teacher preparation institution in southern Thailand. This action research followed a process of four stages: (1) plan, (2) act, (3) observe, and (4) reflect. Each cycle involved reflecting on the outcomes to revise and improve teaching practice. The research was conducted over 64 hours, through 11 lesson plans. Data were collected using post-lesson reports, semi-structured interview, lesson plans, students’ diaries, and classroom observations. Qualitative data were analyzed through content analysis. The study identified seven best practices for promoting science student teachers’ TPACK in life science: (1) surveying challenging life science topics, (2) building a clear understanding of TPACK, (3) demonstrating TPACK-based lessons, (4) designing and refining lesson plans with expert guidance, (5) engaging in microteaching and real-class teaching, (6) reflecting on teaching practices through self and peer evaluations, and (7) revising lesson plans based on feedback. These practices provide an effective framework for integrating technology, pedagogy, and content knowledge in life science.